Binding of heat shock factor to and transcriptional activation of heat shock genes in Drosophila. - Fernandes, M.; Xiao, H.; Lis, J.T. (Nucleic Acids Research, 1995)
Heat shock factor (HSF) binds to heat shock elements (HSEs) and the binding can be highly cooperative. Here we report an analysis of binding of Drosophila HSF to both native and synthetic heat shock regulatory regions. We find that cooperative binding of HSF requires close proximity, rather than helical alignment, of HSEs. Two or more trimeric HSEs organized as contiguous 5 bp units show much higher levels of cooperativity than multiple but separated HSEs. We discuss these in vitro observations in the context of the in vivo status of heat shock genes under mild and full heat shock conditions. Finally, we show that the DNA binding and trimerization domains alone may be sufficient for the full level of binding cooperativity between HSF trimers. This last result suggests that close proximity of HSEs for cooperative binding of HSF is a result of protein-protein interactions near the point of DNA contact.